Antecedents and Consequences of Employee Engagement - Rahayu Utaminingsih; Ratno Purnomo (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
This research is a study of the antecedents and consequences of employee engagement that is focused on the sample which is a generation Y. This study was conducted on operational employees working in the field of hospitality. This study takes the title: